Empirical studying of gender distinctions of students-psychologists in the relation to personal and professional qualities of the psychologist - A B Kosareva (RUDN Journal of Psychology and Pedagogics, 2009)
In work the flight research directed on revealing of representations at students-psychologists about individually-personal and is professional-important qualities of the expert-psychologist is analysed.